Freshwater zooplankton of Bakun dam Sarawak, Malaysia - Shabdin, Mohd Long (Asian Journal of Biological and Life Sciences, 2014)
Bakun Dam was fully reached its supply level of 228 m above sea level (ASL) on 9 March 2012. Since it form a reservoir, no report on zooplankton is published. Therefore, initiative has been made to study the zooplankton community and its relation to the subsurface water parameters in the reservoir. Subsurface zooplankton is sampled using plankton net and water parameters are measured using Eutech Instrument. The water parameters recorded in Bakun dam reflected the freshwater lake in tropical countries. Five species of zooplankton are recorded in Bakun Dam, namely Neodiaptomus handeli, Tropodiaptomus sp. Daphnia sp., Ceriodaphnia cornuta and Brachionus quadridentatus splendidus. Calanoida was dominant (maximum value: 20.49x106) in Bakun Dam, followed by Cladocera (maximum value: 8.91 x106) and Ploima (Rotifera) (maximum value: 1.77x106). The water temperature influenced the species diversity and evenness of zooplankton. The suitable water temperature in the reservoir possibly increases the phytoplankton densities which serves as food and enhance the density of zooplankton. Furthermore, with low number of zooplankton species, the competition for food amongst the species is also less, thus the opportunist species has an opportunity to increase their population rapidly and become dominant in the area.